Blood Pressure Target in Acute Stroke to Reduce HemorrhaGe After Endovascular Therapy: The Randomized BP TARGET Study Protocol - Mazighi, Mikael; Labreuche, Julien; Richard, Sebastien; Gory, Benjamin; Lapergue, Bertrand; Sibon, Igor; Berge, Jerome; Olivot, Jean-Marc; Reiner, Peggy; Houdart, Emmanuel; Broderick, Joseph; Duhammel, Alain; et al. (Frontiers in Neurology, 2020)
Background: High systolic blood pressure (BP) is associated with an increased risk of intracranial hemorrhage (ICH) in patients undergoing reperfusion therapy. However, there are no data from randomized trials to guide BP management after reperfusion following endovascular therapy (EVT) for acute ischemic stroke (AIS) patients with large vessel occlusion (LVO). The objective is to evaluate if BP control with a target of 100-129 mmHg systolic BP (“tight” SBP control) can reduce ICH as compared to 130-185 mmHg (“usual” SBP control) in AIS participants after reperfusion by EVT. Methods The BP TARGET trial is a multicenter, prospective, randomized, controlled, open-label, blinded end-point clinical trial. AIS subjects with LVO experiencing successful reperfusion, are randomly assigned, in a 1:1 ratio, to have a “tight” SBP control (100-129 mmHg) or a conservative SBP control (130-185 mmHg) during the following 24-36 hours. The primary outcome is the rate of ICH (either symptomatic or asymptomatic) on follow-up CT scan at 24-36 hours. Secondary outcomes include the rate of the symptomatic ICH, the overall distribution of the modified Rankin Scale (mRS) at 90 days, favourable outcome (90-day mRs 0-2), infarct volume at follow-up CT scan at 24-36 hours, the change in National Institute of Health Stroke Scale at 24 hours and all-cause mortality at 90 days. Conclusion This is the first randomized trial directly comparing the efficacy of different SBP targets after EVT reperfusion. This prospective trial aims to determine whether a “tight” SBP control after EVT reperfusion can reduce the risk of ICH.